KAJIAN MUTU LABU SIAM (Sechium edule) TEROLAH MINIMAL YANG DIKEMAS VAKUM SELAMA PENYIMPANAN - Pinem, Esron H.; Longdong, Ireine A.; Lengkey, Lady C. Ch. E. (Jurnal Teknologi Pertanian (Agricultural Technology Journal, 2020)
AbstractThis study aims to analyze the deterioration of the quality of the chayote during storage using several packaging methods. The research method was carried out experimentally and the data were processed descriptively which consisted of three treatments, namely: vacuum packed, without vacuum, and open. Each treatment was carried out 3 (three) times with each weight of 250 grams. Research shows that minimally processed chayote which is vacuum packed and stored at a temperature range of 5oC - 9.6oC can last for 12 days, experiencing a weight loss of 0.90%. The color changed from Faded Yellow to Gray Yellow. The texture becomes soft with a hardness value of 8.80 N. The water content changes from 91.98% to 94.70%.In conclusion, the storage life of vacuum packed minimally processed chayote could be prolonged up to 12 days at 5oC â€“ 9,6oC, grey-yellow in color, texture softened, and weight loss as much as 0.90%.Â Keywords: Chayote, minimally processed, vacuum packed.